Leadership as a core creativity for musician identity - Bennett, Dawn; Rowley, J.; Reid, A. (2017)
Leadership development and musician identities are complex ideas that may be understood from theoretical and practical perspectives, and yet rarely are they explicitly addressed within higher music education. This paper draws on complexity theory to probe these perspectives. It does so within the context of an internship program designed to offer student musicians authentic workplace experiences. Complexity theory suggests that across multiple domains there are often three elements that enable the diverse situations to cohere. In this case, student musicians’ movement through multiple domains exposed three connective elements: namely, bridging the gap between theory and practice, flexibility, and reorienting learning as career relevance is realised. The inclusion of experiential learning in the education of professional musicians enabled the student musicians to develop essential, transferable skills such as leadership, communication, teamwork, workplace negotiation and problem solving. Moreover, students learned to re-imagine what their musical world might mean and how their own capabilities and creativity might come to the fore as leaders. This learning was evidenced in students’ reflections on this important professional experience. The skills identified by students are same skills identified by employers as being vital to successful transition to a career, and the same skills identified by practising musicians as vital to leading complex careers within and beyond the music industry, often from the point of graduation. The paper reveals how students experience the liminal space between formal music study and internship work experiences and how, in turn, they transform their thinking from situation to situation.